High-Resolution Imaging and Spectroscopy at High Pressure: A Novel Liquid Cell for the Transmission Electron Microscope. (December 2015) - Tanase, Mihaela; Winterstein, Jonathan; Sharma, Renu; Aksyuk, Vladimir; Holland, Glenn; Liddle, James A.
Abstract: We demonstrate quantitative core-loss electron energy-loss spectroscopy of iron oxide nanoparticles and imaging resolution of Ag nanoparticles in liquid down to 0.24 nm, in both transmission and scanning transmission modes, in a novel, monolithic liquid cell developed for the transmission electron microscope (TEM). At typical SiN membrane thicknesses of 50 nm the liquid-layer thickness has a maximum change of only 30 nm for the entire TEM viewing area of 200×200 µ m.